Preparation, structure–property relationships, and applications of novel bio-based and biodegradable polyesteramide materials - Xipo Zhao; Fan Mo; Caibo Zhao; Shunmei Li; Min Wang; Shixing Dong; Ling Zhou (npj Materials Degradation)
Abstract Poly(ester amide) (PEA), which contains ester (–COO–) and amide (–NHCO–) bonds in its molecular chain, is anticipated to exhibit excellent biodegradability, biocompatibility, mechanical strength, and processability through meticulous monomer selection and molecular structure design. As a novel material with significant research value and broad application potential, PEA has garnered increasing attention. This review comprehensively examines recent advancements in bio-based and biodegradable PEA materials, focusing on the effects of bio-based monomers, synthesis methods, and molecular structural parameters-including molecular configuration, sequence architecture, and intermolecular forces on material properties. PEAs derived from α-amino acids, vegetable oils, and plant polysaccharide polyols are highlighted, alongside a detailed comparison of key preparation techniques such as polycondensation, ring-opening polymerization, and enzymatic polymerization. Moreover, the relationships between molecular structures and the thermal, mechanical, and degradation properties of PEAs are thoroughly analyzed. The applications of PEA materials in diverse fields, including drug delivery and tissue engineering in the medical domain, as nanofiltration membranes in separation technologies, and as coatings, are systematically summarized. This review provides valuable insights into the structural design of PEA materials, strategies for regulating biodegradability and functionality, and opportunities for expanding application areas.